Efektifitas Terapi Jahe Hangat Dalam Mengatasi Emesis Gravidarum Pada Ibu Hamil: The Effectiveness of Warm Ginger Therapy in Overcoming Emesis Gravidarum In Pregnant Women - Wijaya; Yuliana; Magdalena Agu Yosali; Noor Siti Noviani Indah Sari; Rizka Sulistyaningsih; Tety Novianty; Eni Rizki Rahayu (LPPM STIKES Guna Bangsa Yogyakarta, 2023)
According to the World Health Organization (WHO), hyperemesis gravidarum occurs worldwide, including in the United States, with an incidence of 0.5-2%, Sweden 0.3%, California 0.5%, Canada 0.8%, China 10.8%, Norway 0.9%, Pakistan 2.2% and Turkey 1.9%. Currently, the incidence of hyperemesis gravidarum in Indonesia is 1-3% of all pregnancies. The aim of this research is to determine the effectiveness of administration of warm ginger on the incidence of gestational vomiting in pregnant woman in early pregnancy. It was a quantitative study with a pre-experimental study design using one group pretest-posttest design. The study population consisted only of pregnant women in the first trimester who suffered from morning sickness and whose pregnancies were assessed with the BPM Happy Purnama. Sampling for this study used a global sampling technique with a sample of 16 individuals. Data were collected using the Vomiting Pregnancy-Specific Quantification Questionnaire. The statistical results of the study showed a p-value of 0.002. This means less than a significant value that is less than 0.05. Therefore, it can be concluded that the administration of hot ginger effectively reduced the frequency of pregnancy vomiting. This study is also intended to be an alternative non-pharmacological treatment for vomiting in pregnant women in the first trimester.